Sveti Maksim Grk (Mihail Trivolis, Arta, ok. 1469– Maksim Grk, Moskva, 1556) in njegov molitveni nagovor Matere Božje - Zajc, Neža (Bogoslovni vestnik, 2024)
This paper examinesthe knowledge, relationship and outlook of St Maximus the Greek towards the Mother of God on the basis of his “Prayer to the Mother of God”. A comprehensive literary and theological analysis, based on a critical reading of the original manuscripts, encompasses a detailed and suggestive comparison of the Byzantine patristic and liturgical traditions. Furthermore, insight is provided into select additional writings of Maximus relevant to the topic, which, in conjunction with the aforementioned prayer, facilitate a more precise understanding of his relationship to the Mother of God. It is also crucial to consider his profound reception of the biblical message as presented in both the Old and New Testaments. The author’s primary concern is the consolation and purification of the souls of all believers, which can only be achieved through the prayerful intercession of Mary. The text is addressed to the reader, who is presumed to be a believer or a monk. In this way, the contribution constitutes an essential element in the reconstruction of Maximus the Greek’s euchology, which cannot be separated from his monastic experience in the Monastery of Vatopaidi on the Holy Mount Athos. Indeed, his prayer practice, together with the Byzantine tradition, originated in his monastic self- -identification.
Keywords: biblical message; biblično sporočilo; euchology; evhologija; Maksim Grk; Maximos the Greek; molitev; molitvena praksa; Old Testament; prayer; prayer practice; Stara zaveza